Emodin in cardiovascular disease: The role and therapeutic potential - Yuanyuan Guo; Yuanyuan Guo; Rongzhen Zhang; Wenlan Li (Frontiers Media S.A., 2022)
Emodin is a natural anthraquinone derivative extracted from Chinese herbs, such as Rheum palmatum L, Polygonum cuspidatum, and Polygonum multiflorum. It is now also a commonly used clinical drug and is listed in the Chinese Pharmacopoeia. Emodin has a wide range of pharmacological properties, including anticancer, antiinflammatory, antioxidant, and antibacterial effects. Many in vivo and in vitro experiments have demonstrated that emodin has potent anticardiovascular activity. Emodin exerts different mechanisms of action in different types of cardiovascular diseases, including its involvement in pathological processes, such as inflammatory response, apoptosis, cardiac hypertrophy, myocardial fibrosis, oxidative damage, and smooth muscle cell proliferation. Therefore, emodin can be used as a therapeutic drug against cardiovascular disease and has broad application prospects. This paper summarized the main pharmacological effects and related mechanisms of emodin in cardiovascular diseases in recent years and discussed the limitations of emodin in terms of extraction preparation, toxicity, and bioavailability-related pharmacokinetics in clinical applications.